THE HISTORY OF LIMIT: FROM GEOMETRY AND NUMBER SEQUENCE PERSPECTIVE - Rahmania Yuwono, Layli
This project explores some classical mathematics problems from ancient Greece and the 17th century. The problems to be studied are the ratio of the areas of two circles solved by Eudoxus, the area of parabolic segment solved by Archimedes, and the construction of sequences of approximating a non perfect square roots solved by Girard. This project involved an analysis of the mathematical content based on historical contextual which focused on problem-solving. The literary sources used are the indirect sources such as article paper, books, and other literature. The results of research on these issues can be used as recommendations to teachers as one of alternative teaching materials which help students initially understand the limit concept.